A digital intervention to reduce home-office workers’ sedentary behaviour: protocol for the evaluation of the Click2Move programme, a cluster randomised controlled trial - Judit Bort-Roig; Iris Parés-Salomón; Bette Loef; Cristina Vaqué-Crusellas; Alan Coffey; Arnau Gustems-Morral; Anna M. Señé-Mir; Izabela Luznik; Maja Pajek; Kieran P. Dowd; Anna Puig-Ribera; Karin I. Proper (BMC Public Health)
Abstract Background A new paradigm of hybrid working exists, with most office workers sharing their work between the office and home office environment. Working from home increases time spent or prolonged sitting, which is associated with an increased risk of chronic disease. Interventions to reduce sitting time, specifically designed for both the office and home-office environments, are required to address this growing public health issue. This study presents a protocol to evaluate the effectiveness of a digital intervention (Click2Move) to reduce sitting time and improve employees’ health and occupational wellbeing among hybrid office workers. Methods A two-arm cluster randomised controlled trial will be undertaken among hybrid office employees. In total, 200 employees will be recruited across four companies across Europe (The Netherlands, Spain, Ireland, and Slovenia). Participants within each company will be randomly allocated to the intervention or control group at the unit/cluster level. The intervention group will receive the novel multicomponent Click2Move intervention (including environmental, organisational, and individual strategies) for 12 months, and the control groups will maintain their usual work practices. The primary outcome will be occupational sedentary time measured via activPAL3TM at baseline and at 3, 6 and 12 months follow-up. Secondary outcomes will include device-based (activPAL3TM) and self-reported (Global Physical Activity Questionnaire and Workforce Sitting Questionnaire) physical activity and sedentary behaviour; self-reported musculoskeletal disorders (Standardised Nordic Questionnaire) and pain (Numeric Rating Scale); self-reported presenteeism and absenteeism (Health and Work Performance Questionnaire), job satisfaction (Need for Recovery scale) and fatigue (single-item 5-point Likert scale). Focus groups will be conducted with employees post-intervention. Linear mixed models, accounting for covariates, will be employed to determine the effects of the intervention. Additionally, we will perform a full process evaluation analysis. Discussion The proposed study will offer a comprehensive evaluation of a digital intervention aimed at reducing sedentary behaviour among hybrid office workers, offering practical solutions to enhance the health, wellbeing and productivity of a growing segment of the workplace. Trial registration ClinicalTrials.gov NCT06247228. Registered 30 January 2024.